Konsep Kebijakan Moneter dalam Perspektif Ekonomi Islam - Dini Abdianti; Anisa Restu; Sholahuddin Al Ayyubi; Faisal Hidayat (Universitas 45 Surabaya, 2023)
Monetary policy in Islamic economics is part of the branch of economics that discusses the nature, function and influence on economic activity in a country. Monetary in Islam does not emphasize not only the supply and demand for money, but also the principles of equity and brotherhood, which seek equality and create a fair distribution of wealth and income. The method of writing this article uses a qualitative research approach. The data analysis technique is in the form of descriptive analysis. Descriptive itself is a research result that is described as clearly as possible based on research. Monetary policy can maintain economic stability, this can be seen by balancing the amount of money that is widely spread in a balanced way. If any money in circulation exceeds or is greater or less than a number of goods and services, then the economy in a country will be chaotic.